2019
DOI: 10.3390/nu11091965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steviol Glycosides on Human Health with Emphasis on Type 2 Diabetic Biomarkers: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The natural sweetener from Stevia rebaudiana Bertoni, steviol glycoside (SG), has been proposed to exhibit a range of antidiabetic properties. The objective of this systematic review was to critically evaluate evidence for the effectiveness of SGs on human health, particularly type 2 diabetic (T2D) biomarkers, collecting data from randomized controlled trials (RCTs). Electronic searches were performed in PubMed and EMBASE and the bibliography of retrieved full-texts was hand searched. Using the Cochrane criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 65 publications
(166 reference statements)
1
25
0
4
Order By: Relevance
“…Stevia glycosides possess impressive antidiabetic effect in preclinical assays; however, they could not impress in clinical studies [140]. It has been revealed that the doses were not sufficient to achieve anticipated pharmacological effect [140], which may be correlated to that of poor bioavailability issue of Stevia glycosides.…”
Section: Stevia Glycosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stevia glycosides possess impressive antidiabetic effect in preclinical assays; however, they could not impress in clinical studies [140]. It has been revealed that the doses were not sufficient to achieve anticipated pharmacological effect [140], which may be correlated to that of poor bioavailability issue of Stevia glycosides.…”
Section: Stevia Glycosidesmentioning
confidence: 99%
“…Stevia glycosides possess impressive antidiabetic effect in preclinical assays; however, they could not impress in clinical studies [140]. It has been revealed that the doses were not sufficient to achieve anticipated pharmacological effect [140], which may be correlated to that of poor bioavailability issue of Stevia glycosides. Over the year, several nanoformulations of Stevia glycosides have been formulated, which were found to enhance the oral bioavailability, target specificity, and therapeutic efficacy of the Stevia glycosides [111].…”
Section: Stevia Glycosidesmentioning
confidence: 99%
“…Sugar containing products should be used in moderation (sugar less than 10 E%) due to their potential effects on glucose control, and in long-run, body weight control, as well. New sweeteners may offer some additional benefits [15]. Regarding the intake of fat in diabetic patients, both the quality and quantity of fat are in line with the general recommendations regardless of the type of diabetes [4].…”
mentioning
confidence: 55%
“…However, large heterogeneity was found due to different treatment patterns for aspartame and sugar or water. Similarly, meta-analysis, based on RCTs, showed no effect of steviol glycoside consumption on BMI compared to talcum, maize starch, or unspecified matching placebo in healthy individuals and patients with diabetes ( 35 ). Additionally, subgroup analyses showed no significant effect of steviol glycoside on BMI in either healthy individuals and patients with diabetes.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…No significant effect on glucose levels and glycated hemoglobin (HbA1c) levels were found after acute or long-term aspartame consumption ( 39 , 40 , 43 50 ) ( Table 2 ). Similarly, a meta-analysis of long-term RCTs showed no effect of steviol glycoside on glucose levels and HbA1c levels in healthy individuals and patients with diabetes ( 35 ). Regarding other artificial sweeteners, glucose levels were not found to be affected by acute saccharin consumption in healthy individuals and patients with diabetes, and acute acesulfame-K consumption in healthy individuals ( 39 , 43 ).…”
Section: Glucose Homeostasismentioning
confidence: 99%